O Ministério Público como catalisador das demandas sociais e a efetividade das soluções negociadas - Fávaro, Daniela Moysés da Silveira (2024)
Since the emergence of the Social and Democratic Rule of Law, the issue of access to justice has gained new contours. The affirmation of social and collective rights, making the positive benefits of the State mandatory, made it necessary to create new mechanisms in the field of jurisdiction for the due protection of the new demands that arose and transformed the role of the institutions responsible for the satisfaction of rights, in cases of violation or inertia of the other powers. The Judiciary has become more gigantic than the other institutions, which has not necessarily resulted in the effectiveness of social rights. The creation of the collective process, in this context, was certainly a step forward. However, as we have tried to demonstrate, the provisions in the field of collective protection of social rights require not only instruments of democratic participation but also a change in the mentality of those who apply the law. The Public Prosecutor's Office, after the promulgation of the 1988 Constitution, became one of the constitutional institutions of social promotion; It is the universal legitimacy – and the most active and proactive – for the defense of social and collective rights. The objective of the dissertation was to demonstrate that, for the fulfillment of its missions. It is essential to use special and exclusive instruments, which enable its preventive and resolute action, in the protection of the public interest. To this end, detailed theoretical research was carried out on instruments that allow the establishment of a democratic dialogue not only for control but also in the induction of public policies aimed at the realization of social rights. In conclusion, the examples of resolute action demonstrate how effective the extrajudicial action of the institution can be in the defense of society's interests, when exercised with emphasis on the function and task of enforcing the Constitution and fundamental rights and in conforming the State to the ideology and the table of constitutional values